Straits Settlements Blue Book (imports/exports) s1911-1912 vol. 56-57 (Great Britain : Public Record Office, 1971)
Mengandungi'Statement of the quantities and value of imports and exports of the colony of the Straits Settlements from and to other countries in 1910 and 1911';'Blue Book for the year 1912'.